2018
DOI: 10.29238/teknolabjournal.v7i1.110
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulator of Ethanol Extracts of The Leaves Azadirachta indica Against Macrophage Peritoneal Cell in Mice Induced The Vaccine BCG

Abstract: P a g e | 9 yang diinduksi vaksin BCG, sehingga ekstrak etanol daun mimba dapat diaplikasikan pada penderita tuberkulosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…The dried neem leaves were crushed and ground using a grinder and then sieved to obtain a powder form. According to Abror et al (2018), the neem extraction step was done by soaking neem leaf powder in 70% ethanol for 3x24 hours. The extract obtained was then filtered.…”
Section: Preparation Of Neem Leaf Ethanol Extract (A Indica)mentioning
confidence: 99%
“…The dried neem leaves were crushed and ground using a grinder and then sieved to obtain a powder form. According to Abror et al (2018), the neem extraction step was done by soaking neem leaf powder in 70% ethanol for 3x24 hours. The extract obtained was then filtered.…”
Section: Preparation Of Neem Leaf Ethanol Extract (A Indica)mentioning
confidence: 99%
“…There is an immunomodulatory effect of neem leaf (A. indica A. Juss) ethanol extract on the peritoneal macrophage cell number in mouse-induced BCG vaccine in which macrophages are innate immunity that serves as an initial defense against infection by phagocytosis process. It also plays an important role as the Antigen Presenting Cell (APC) that initiates and directs immunity to the cellular immune system [15]. Based on these facts in the framework of the cultivation development activities, especially for tilapia, it is necessary to evaluate the ethanol fraction of neem leaf (A. indica A. Juss) on immunostimulant activity of tilapia Oreochromis niloticus.…”
Section: Immunostimulant Activity Of Neem Leaf Ethanol Fraction On Timentioning
confidence: 99%
“…These compounds showed anticancer activity [7]. Numerous studies of neem bioactivities covered many topics, including antibacterial [3,8], antioxidant [9,10], anticancer [11], and immunomodulatory activities [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Immunomodulation of the neem leaf extract occurred by altering the peritoneal macrophages population in experimental animals [13]. Research found that extract of neem leaves enabled to stimulation of expression of IFN and components of immune surveillance cells (NK cell, T cytotoxic cell (CD8 + ), and macrophage) as observed in benzo(a)pyrene-induced mice [12].…”
Section: Introductionmentioning
confidence: 99%